High PRAME expression is associated with poor survival and early disease progression in myelodysplastic syndromes with a low bone marrow blast percentage. Issue 10 (24th August 2021) - Shiseki, Masayuki; Ishii, Mayuko; Ohwashi, Mari; Wang, Yan-Hua; Tanaka, Norina; Osanai, Satoko; Yoshinaga, Kentaro; Mori, Naoki; Tanaka, Junji
Abstract: We investigated the clinical implications of pr eferentially expressed a ntigen in me lanoma (PRAME) expression in bone marrow cells of 116 patients with myelodysplastic syndromes (MDS). Quantitative RT-PCR was carried out to examine the PRAME expression level. High PRAME expression was observed in MDS patients classified into higher revised International Prognostic Scoring System (IPSS-R) risk categories (Very high and High) with a high bone marrow blast percentage (5% or higher). Kaplan-Meier analysis demonstrated that high PRAME expression is significantly associated with a poorer overall survival (OS) in MDS patients with a low bone marrow blast percentage (less than 5%) (log-rank test p  = .0014) and those classified into lower IPSS-R risk categories (Very Low, Low, and Intermediate) (log-rank test, p  = .0035). In contrast, there was no significant association between PRAME expression and OS in MDS patients with a high bone marrow blast percentage or those classified into higher IPSS-R risk categories. In addition, high PRAME expression was associated with early disease progression in MDS patients with a low bone marrow blast percentage. This study suggested PRAME expression to be a prognostic factor in MDS.